2007
DOI: 10.1021/la062326c
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled Nanowire Networks of Aryloxy Zinc Phthalocyanines Based on Zn−O Coordination

Abstract: Tetrakis(aryloxy)phthalocyanine (4c) and its Zn congeners (4a and 4b) and Ni congener (4d) were synthesized, and their self-assembling properties in coordinating and non-coordinating solvents were investigated by absorption and fluorescence spectroscopy, matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF MS), and transmission electron microscopy (TEM). Compounds 4a and 4b in non-coordinating solvents exhibit red-shifted and split Q-bands in absorption spectra even at very l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 51 publications
2
45
0
1
Order By: Relevance
“…One of the distinct spectroscopic properties of J-aggregations is a sharp excitonic absorption peak called the J-band, red-shifted from the monomer band [24] . As we have reported previously [7] , α-aryl/ alkoxy-substituted zinc Pcs could form J-aggregation through intermolecular Zn-O coordination in non-coordinating solvents such as chloroform and toluene. However, it did not work in coordinating solvents such as THF, DMF, and ethanol.…”
Section: Resultssupporting
confidence: 55%
See 3 more Smart Citations
“…One of the distinct spectroscopic properties of J-aggregations is a sharp excitonic absorption peak called the J-band, red-shifted from the monomer band [24] . As we have reported previously [7] , α-aryl/ alkoxy-substituted zinc Pcs could form J-aggregation through intermolecular Zn-O coordination in non-coordinating solvents such as chloroform and toluene. However, it did not work in coordinating solvents such as THF, DMF, and ethanol.…”
Section: Resultssupporting
confidence: 55%
“…However, it did not work in coordinating solvents such as THF, DMF, and ethanol. It has already been reported that J-aggregation formed through Zn-O coordination could dissociate upon the addition of methanol [7] . Figure 2(a) shows the absorption spectra of 3-azoZnPc in THF and chloroform solutions.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Thus, UV-Vis spectroscopy has demonstrated the transformation of the monomeric phthalocyanine complexes bearing four peripheral aryloxy substituents to the J-type aggregates upon addition of pyridine to the solutions in chloroform. [6] In the case of the monomeric complexes with only one peripheral polar substituent (e.g. low-symmetry phthalocyanines), instead of aggregates the dimers of similar structure are formed.…”
Section: Introductionmentioning
confidence: 99%